2017
DOI: 10.1158/1535-7163.mct-16-0337
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of MEK and PI3K/Akt Rescues Cancer Cachexia through both Tumor-Extrinsic and -Intrinsic Activities

Abstract: Involuntary weight loss, a part of the cachexia syndrome, is a debilitating co-morbidity of cancer and currently has no treatment options. Results from a recent clinical trial at our institution showed that biliary tract cancer patients treated with a MEK inhibitor exhibited poor tumor responses, but surprisingly gained weight and increased their skeletal muscle mass. This implied that MEK inhibition might be anti-cachectic. To test this potential effect of MEK inhibition, we utilized the established Colon-26 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 59 publications
3
37
1
Order By: Relevance
“…Additionally, he showed that growth differentiation factor 15 (GDF‐15) is required for development of pancreatic cancer KPP and GDF‐15fl/fl mice exhibit a reduction in pancreatic cancer. Moreover, KPP mice at their endpoint exhibited decreased body weight compared with their littermate controls but, importantly, had similar tibia lengths, suggesting that the lower body weights of KPP mice were not due to a failure to grow . The KPP mouse as an improvement over existing animal models of cachexia and anticipate that KPP mice will prove to be a useful tool in improving our understanding of the mechanisms driving tissue wasting and in translating that understanding into new anti‐cachexia therapies …”
Section: Basic Sciencementioning
confidence: 98%
“…Additionally, he showed that growth differentiation factor 15 (GDF‐15) is required for development of pancreatic cancer KPP and GDF‐15fl/fl mice exhibit a reduction in pancreatic cancer. Moreover, KPP mice at their endpoint exhibited decreased body weight compared with their littermate controls but, importantly, had similar tibia lengths, suggesting that the lower body weights of KPP mice were not due to a failure to grow . The KPP mouse as an improvement over existing animal models of cachexia and anticipate that KPP mice will prove to be a useful tool in improving our understanding of the mechanisms driving tissue wasting and in translating that understanding into new anti‐cachexia therapies …”
Section: Basic Sciencementioning
confidence: 98%
“…(Department of Cancer Biology and Genetics, The Ohio State University Wexner Medical Center, Columbus, OH, USA) gave an overview to the important functions of NF‐κB in myoblast to stimulate activin and inhibit muscle differentiation. They impressively showed that NF‐κB is activated in cachectic muscle in both paired box 7 progenitor cells and myofibers . Other studies buttress the view that increased forkhead box protein O (FoxO) signalling and the activation of the transcription factors NF‐κB, muscle RING finger 1 (MuRF1), and muscle atrophy F‐box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression .…”
Section: Basic Sciencementioning
confidence: 99%
“…(Department of Cancer Biology and Genetics, The Ohio State University Wexner Medical Center, Columbus, OH, USA) gave an overview to the important functions of transcription factors nuclear factor κB (NF‐κB) in myoblast to stimulate activin and inhibit muscle differentiation. He impressively showed that NF‐κB is activated in cachectic muscle in both PAX 7 progenitor cells and myofibers . Other studies buttress the view that increased forkhead box protein O (FoxO) signalling and the activation of the transcription factors NF‐κB, MuRF1 and muscle atrophy F‐box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression .…”
Section: Basic Sciencementioning
confidence: 99%